Choosing a monetary value of greenhouse gases in assessment tools: A comprehensive review. (20th July 2016) - Isacs, Lina; Finnveden, Göran; Dahllöf, Lisbeth; Håkansson, Cecilia; Petersson, Linnea; Steen, Bengt; Swanström, Lennart; Wikström, Anna
Abstract: There is a societal need for using monetary estimates of social impacts of CO2 and other greenhouse gases in different assessment tools, such as cost-benefit analysis and life-cycle assessment. A number of estimates are available in the literature. Since these differ by several orders of magnitude, there is ambiguity and confusion about which to use. This review aims to give some guidance on this issue. The variation in carbon value estimates depends on several uncertain aspects – which will remain uncertain – including climate sensitivity, assumptions about future emissions, and decision makers' ethical standpoints. Hence, there is no single correct monetary value for CO2 : it will depend on the ethical standpoint of the user. Due to this, estimates of social costs of CO2 emissions cannot be used for calculating an optimal emission level, although they can inform such assessments. It is suggested that marginal abatement cost values are used for emissions capped by binding targets in short-term assessments, and that social cost of carbon values should be used for all other emissions. Benchmark principles for choosing a monetary carbon value are suggested along with associated estimates. Depending on the choices made with regard to ethical standpoints and assumptions about future emissions and climate sensitivity, estimates can be significantly higher than the ones typically used in assessment tools today. The estimates need continuous updating, and there is need for better understanding and communication around the limitations and uncertainties involved. Highlights: There is no single correct monetary value for CO2 ; it will depend on the ethical standpoint of the user. Major value determinants will stay uncertain, and subjective, which is why final estimates will too. Estimates can be significantly higher than those typically used in assessment tools today. MAC values are suggested for emissions under binding targets; SCC values apply to all other. Principles for choosing a CO2 value are suggested, along with associated estimates.